Can xylene and quercetin directly affect basic ovarian cell functions?. (August 2018) - Tarko, Adam; Štochmalova, Aneta; Hrabovszka, Sandra; Vachanova, Adriana; Harrath, Abdel Halim; Alwasel, Saleh; Grossman, Roland; Sirotkin, Alexander V.
Abstract: Exposure to xylene leads to dysfunction of mammalian female reproduction. Quercetin present in vegetables contribute significantly to their role as health-promoting foods. The effects of xylene and quercetin on ovarian cell function, their interrelationships, and mechanisms of action are insufficiently studied. In this in vitro study, we examined the effects of xylene, quercetin, and xylene/quercetin combination on basic bovine ovarian cell functions, such as proliferation, apoptosis, and hormone release. Furthermore, we examined the protective effect of quercetin against the potential negative effects of xylene. Proliferation and apoptosis were assessed via immunocytochemistry using PCNA and BAX markers. The release of progesterone, testosterone, and insulin-like growth factor (IGF–I) was analysed by EIA/RIA. Xylene stimulated proliferation and IGF-I release, but inhibited progesterone and testosterone release. Quercetin inhibited proliferation, apoptosis, and release of IGF–I, progesterone, and testosterone. When administered with xylene, quercetin prevented the action of xylene on proliferation and IGF-I release, induced the stimulatory action of xylene on apoptosis, and promoted the effect of xylene on release of progesterone but not testosterone. These results demonstrated the actions of both xylene and quercetin on basic ovarian cell functions. Furthermore, they show, that quercetin can either prevented or promote xylene effects on the ovarian cells, which indicates potential usefulness of quercetin for prevention of xylene action on female reproduction. Graphical abstract: Highlights: Our results demonstrated the actions of both xylene and quercetin on ovarian cell functions. Xylene promoted ovarian cell proliferation and IGF-I release but inhibited progesterone and testosterone release. When administered alone, quercetin inhibited all the examined ovarian cell functions. Moreover, quercetin prevented some effects of xylene (proliferation and IGF-I release), while promoting other effects (progesterone release and stimulatory effect on apoptosis), suggesting that quercetin could be used for the prevention of certain effects of xylene on reproductive processes. Furthermore, it is the first demonstration that quercetin was able to modify xylene effect on ovarian cell, whilst in some cases it was not able to prevent effect of contaminant. I believe, our studies could contribute to understanding the mechanisms of negative effects of environmental contaminants on female reproduction, as well as to prevention or treatment of this effect by using quercetin as functional component of food plants.